Similar Interactions of the Poliovirus and Rhinovirus 3D Polymerases with the 3′ Untranslated Region of Rhinovirus 14 - Meredith, Janet M. (American Society for Microbiology, 1999)
We showed previously that a human rhinovirus 14 (HRV14) 3′ untranslated region (3′ UTR) on a poliovirus genome was able to replicate with nearly wild-type kinetics (J. B. Rohll, D. H. Moon, D. J. Evans, and J. W. Almond, J. Virol 69:7835–7844, 1995). This enabled the HRV14 single 3′ UTR stem-loop structure to be studied in combination with a sensitive reporter system, poliovirus FLC/REP, in which the capsid coding region is replaced by an in-frame chloramphemicol acetyltransferase (CAT) gene. Using such a construct, we identified a mutant (designated mut4), in which the structure and stability of the stem were predicted to be maintained, that replicated very poorly as determined by its level of CAT activity. The effect of this mutant 3′ UTR on replication has been further investigated by transferring it onto the full-length cDNAs of both poliovirus type 3 (PV3) and HRV14. Virus was recovered with a parental plaque phenotype at a low frequency, indicating the acquisition of compensating changes, which sequence analysis revealed were, in both poliovirus- and rhinovirus-derived viruses, located in the active-site cleft of 3D polymerase and involved the substitution of Asn18 for Tyr. These results provide further evidence of a specific interaction between the 3′ UTR of picornaviruses and the viral polymerase and also indicate similar interactions of the 3′ UTR of rhinovirus with both poliovirus and rhinovirus polymerases.